2010
DOI: 10.1094/mpmi-23-7-0915
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern Suggests a Role of MiR399 in the Regulation of the Cellular Response to Local Pi Increase During Arbuscular Mycorrhizal Symbiosis

Abstract: Many plants improve their phosphate (Pi) availability by forming mutualistic associations with arbuscular mycorrhizal (AM) fungi. Pi-repleted plants are much less colonized by AM fungi than Pi-depleted plants. This indicates a link between plant Pi signaling and AM development. MicroRNAs (miR) of the 399 family are systemic Pi-starvation signals important for maintenance of Pi homeostasis in Arabidopsis thaliana and might also qualify as signals regulating AM development in response to Pi availability. MiR399 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 42 publications
10
142
0
Order By: Relevance
“…In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013). Thus, it will be interesting to explore whether the application of Pi could reduce the phytoplasma-mediated disease symptoms in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013). Thus, it will be interesting to explore whether the application of Pi could reduce the phytoplasma-mediated disease symptoms in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However these m i R N A s w e r e a l s o r e g u l a t e d b y p h o s p h a t e , p o i n t i n g t o a d i r e c t c o n n e c t i o n b e t w e e n nutrition and symbiosis. Previous studies demonstrated an induction of miR399 under Pi depleted conditions in mycorrhizal M. truncatula and tobacco plants associated with a concomitant increase in Pi content [102] …”
Section: Novel and Specific Mirnas In Beneficial Interactionsmentioning
confidence: 94%
“…It is up-regulated upon Pi starvation to increase the uptake of Pi in Arabidopsis. Overexpression of miR399 causes Pi accumulation in shoots that display Pi toxicity symptoms [39][40][41]. miR396 regulates cell proliferation in developing leaves through the repression of GRF activity and a decrease in the expression of cell cycle genes [42].…”
Section: A) B)mentioning
confidence: 99%